Compatilizer as well as preparation method and application thereof
By using cis-1,2,3,6-tetrahydrophthalic anhydride as graft monomer and nitrogen oxygen stabilized free radical method, the compatibility and interface binding force of POE and nylon are improved, and the existing solutions are solved In the technology, the problem of insufficient melting and boiling points and low grafting rate of the compatible agents has achieved efficient preparation of nylon composite materials and improved mechanical properties.
Patent Information
- Application Number
- CN202411776411.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing maleic anhydride grafting POE compatibilizer has low melting and boiling points, resulting in limited processing technology, easy volatility and degradation, low grafting rate, and small reaction interface during melting and grafting, resulting in large single viscosity Bodies and initiators are difficult to diffuse and affect their mechanical properties.
Cis-1,2,3,6-tetrahydrophthalic anhydride is used as the graft monomer, combined with nitrogen-oxygen stabilized radical method, to increase the graft rate and melt extrusion temperature, avoid monomer volatility and degradation, and React with hydroxyl groups of glass fibers to enhance the interface binding force of nylon composite materials.
The compatibility and interface bonding of POE with nylon is improved, the mechanical properties of composite materials are enhanced, the preparation process is simplified, the cost is reduced, and the residual problems of monomers and initiators are avoided.
Smart Images

Figure CN119241772A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a compatibilizer and a preparation method and application thereof. Background Art
[0002] Polyamide (commonly known as nylon) is a polycondensation polymer compound with amide group repeating units in the main chain of the molecule. It has excellent mechanical properties, processing properties, chemical corrosion resistance and dimensional stability, and is widely used in electronic appliances, automotive engineering plastics, textiles, packaging and other fields. However, for the most commonly used aliphatic nylon 66 and nylon 6, the material itself has the defect of low impact toughness, and in practical applications, it is often necessary to carry out modification treatment, such as physical blending toughening modification, by adding toughening components, such as ethylene propylene diene monomer rubber (EPDM), polyolefin elastomer (POE), polypropylene (PP), polyethylene (PE) and other toughening matrix materials to improve its toughness. However, the above-mentioned toughening group substances, such as POE, are not compatible with polyamide. In practical applications, it is usually necessary to add a compatibilizer to improve the compatibility between the toughening component and the matrix resin. Conventional compatibilizers in the prior art include EPDM grafted maleic anhydride (EPDM-g-MA), POE grafted maleic anhydride (POE-g-MA), PP / PE grafted maleic anhydride (PP / PE-g-MA), etc. Among them, the most common compatibilizer is POE grafted maleic anhydride, which can serve as a bridge to enhance the adhesion and compatibility between polar materials and non-polar materials. Its main application is in the field of nylon modification. Maleic anhydride grafted POE as a compatibilizer can be used in nylon composite materials filled with glass fiber, talcum powder, calcium carbonate, etc., to improve the compatibility and adhesion of the interface between nylon base material and filler, and can greatly improve the mechanical properties of composite materials; when used in nylon, it can significantly improve the toughness of the material and improve the impact strength of the material. The preparation of maleic anhydride grafted POE generally uses peroxide as an initiator, and the grafted monomer maleic anhydride and POE matrix resin are co-mixed and extruded in a twin-screw extruder. Its process flow is characterized by simplicity, convenience and high output, so it is widely used. For example, the maleic anhydride grafted POE provided by Chinese invention patent CN103450403A comprises 94.2-98.5% of a polyolefin elastomer, 0.8-2.0% of maleic anhydride, 0.05-0.5% of a peroxide initiator and 0.15-0.8% of a heat stabilizer, and 0.5-2.5% of an acetone solvent is added, mixed evenly with a high-speed mixer, and then extruded with a single-screw extruder.However, maleic anhydride grafted POE has the following technical problems: First, the melting point (51-56°C) and boiling point (202°C) of maleic anhydride grafted are not high, and it is easy to volatilize and degrade during the actual processing process. It is necessary to add a heat stabilizer to reduce the degradation reaction of maleic anhydride. Moreover, the maleic anhydride reaction is not complete in the molten state, which will cause monomer residues, making the product have a strong odor. The residual peroxide initiator will slowly decompose over time, causing the degradation of the POE matrix resin, and then affecting the mechanical properties; second, the grafting rate of maleic anhydride is not high and the grafting efficiency is low. If the initiator or monomer content is increased, it will cause POE degradation, cross-linking and other problems; third, the traditional method is generally to distribute the grafted monomers and initiators such as maleic anhydride on the POE surface through solutions or liquids such as silicone oil, but POE has a high viscosity during the melt grafting process, and it is difficult for the monomers and initiators to diffuse, so its reaction interface is small, resulting in a low grafting rate.
[0003] Based on the problems existing in the prior art, the present invention further makes technical improvements and provides a compatibilizer on the basis of the prior art, using cis-1,2,3,6-tetrahydrophthalic anhydride as a grafting monomer to replace the maleic anhydride in the prior art to carry out grafting modification of POE. The compatibilizer has high grafting rate and simple preparation process. When used in combination with reinforcing materials containing groups such as hydroxyl groups, such as glass fiber, the interfacial bonding effect between the compatibilizer and nylon can be improved, thereby improving the fusion effect between the compatibilizer and nylon. Summary of the invention
[0004] In order to overcome the deficiencies of the above-mentioned prior art, the purpose of the present invention is to provide a compatibilizer and a preparation method and application thereof, so as to overcome the problems such as the limited processing technology of maleic anhydride in the prior art due to its low melting point and boiling point, and also has the advantages of simple preparation method, low cost and high grafting efficiency.
[0005] To achieve the above objectives, the present invention provides the following technical solutions.
[0006] One aspect of the present invention provides a compatibilizer, which is composed of a polyolefin elastomer, a grafting monomer and an initiator; wherein the grafting monomer is cis-1,2,3,6-tetrahydrophthalic anhydride.
[0007] Preferably, the added amount of the grafting monomer accounts for 2-10 wt % of the polyolefin elastomer.
[0008] Preferably, the initiator is a compound of initiator A and initiator B.
[0009] More preferably, the initiator A is selected from 4,4,5,5-tetramethyl-2-imidazoline-1-oxyl-3-oxide.
[0010] More preferably, the initiator B is at least one selected from dicumyl peroxide, di-tert-butyl peroxide, benzoyl peroxide, tert-butyl perbenzoate, and diisopropyl peroxydicarbonate.
[0011] As a preferred embodiment, the initiator is selected from 4,4,5,5-tetramethyl-2-imidazoline-1-oxyl-3-oxide complexed with diisopropylbenzene peroxide (NITR-DCP).
[0012] Preferably, in the initiator, the mass ratio of the initiator A to the initiator B is: 1: (1~1.2).
[0013] Preferably, the compatibilizer components are as follows, in parts by mass: 100 parts of polyolefin elastomer, 2 to 10 parts of the grafting monomer, and 0.5 to 1 part of the initiator.
[0014] Another aspect of the present invention provides a method for preparing the aforementioned compatibilizer, wherein a polyolefin elastomer, a grafting monomer and an initiator are added to a high-speed mixer for uniform mixing; then, the mixture is fed to a twin-screw extruder through a feed port, reaction conditions are set for reaction and extrusion; finally, the mixture is cooled and pelletized to obtain a grafted product, namely POE-g-TA.
[0015] Preferably, the reaction conditions include a reaction temperature of 200-220° C. and a screw speed of 200-300 rpm.
[0016] Preferably, the feeding speed is 10-20 rpm.
[0017] It can be seen from the above technical scheme that the present invention uses cis-1,2,3,6-tetrahydrophthalic anhydride as a grafting monomer. The melting point of this compound is 101~102℃, and the boiling point is 234.6℃. This monomer has higher melting point and boiling point than maleic anhydride. In particular, it can meet the temperature requirements of melt extrusion during the grafting process, avoiding the volatilization and degradation of the anhydride monomer.
[0018] As one of the aspects of the invention, the present invention also provides the use of the aforementioned compatibilizer in the preparation of modified nylon materials.
[0019] As one aspect of the invention, the present invention also provides a modified nylon material, comprising the aforementioned compatibilizer, nylon, and a toughening agent; the toughening agent is glass fiber.
[0020] Preferably, the modified nylon material comprises, by weight, 50-70 parts of nylon, 25-40 parts of glass fiber, 3-9 parts of the compatibilizer and 0.2-0.4 parts of the antioxidant.
[0021] Preferably, the nylon is nylon 66 or nylon 6; and the antioxidant is antioxidant 1098.
[0022] The compatibilizer (POE-g-TA) prepared by the technical solution of the present invention has TA with both anhydride groups and double bond structures. The anhydride groups can react with hydroxyl-containing glass fibers, while the double bond structure at the other end is entangled with the long chain of nylon through hydrogen bonding, thereby enhancing the compatibility between the glass fiber and nylon.
[0023]
[0024] The technical effects of the technical solution of the present invention are as follows: 1. By adopting the technical scheme of the present invention, the compatibilizer prepared by grafting POE with cis-1,2,3,6-tetrahydrophthalic anhydride, the anhydride monomer can react chemically with the terminal amino group of the polyamide, thereby improving the interfacial bonding force between the dispersed phase and the matrix; at the same time, the anhydride group can also react with the hydroxyl group and other groups on the surface of the glass fiber, and the polyolefin at the other end is entangled with the nylon chain, thereby also improving the interfacial bonding between the glass fiber and the nylon, thereby improving the mechanical properties of the nylon composite material.
[0025] 2. The present invention uses cis-1,2,3,6-tetrahydrophthalic anhydride as a grafting monomer. The melting point of the compound is 101-102°C and the boiling point is 234.6°C. The monomer has a rigid cycloolefin structure with a higher melting point and boiling point, which can meet the temperature requirements of melt extrusion during the grafting process and avoid volatilization and degradation of the anhydride monomer.
[0026] 3. POE grafted cis-1,2,3,6-tetrahydrophthalic anhydride was prepared by the nitrogen-oxide stabilized free radical method, and the monomer grafting rate was increased through "active" free radical polymerization reaction.
[0027] 4. The grafting method adopted in the present invention does not require the addition of other solutions or the use of silicone oil, thereby avoiding the problem of difficulty in diffusion of monomers and initiators caused by the high viscosity of POE during the melt grafting process, thereby improving the grafting rate.
[0028] 5. The compatibilizer provided by the technical solution of the present invention is applied to the modification of thermoplastics, has the advantages of simple operation, easy control, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the infrared spectrum of the compatibilizer POE-g-TA prepared in Examples 1-6 of the present invention. DETAILED DESCRIPTION
[0030] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the protection scope of the present invention.
[0031] The disclosures of all patent and non-patent literature cited herein are incorporated herein by reference in their entirety.
[0032] As used in the invention, the terms "comprise", "include", "contain", "cover", "have", "with" or any other variation thereof are intended to cover non-exclusive inclusions. For example, a process, method, article or device that includes a list of elements is not necessarily limited to those elements, but may include other elements that are not explicitly listed or inherent to the process, method, article or device. In addition, unless expressly indicated to the contrary, "or" refers to an inclusive "or" rather than an exclusive "or". For example, conditions A or B meet any of the following: A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), and both A and B are true (or exist). The phrase "one or more" is intended to cover non-exclusive inclusions. For example, one or more A, B and C, means any of the following: A alone, B alone, C alone, a combination of A and B, a combination of B and C, a combination of A and C, or a combination of A, B and C.
[0033] In addition, "a" or "an" is used to describe the elements and components described herein. This is done only for convenience and to provide a general sense of the scope of the invention. This description should be understood to include one or at least one, one or at least one, and the singular also includes the plural, unless it is obvious that it is intended otherwise.
[0034] The present invention provides a compatibilizer, and the raw materials thereof are proportioned as follows by weight: 100 parts of polyolefin elastomer (POE), 2 to 10 parts of grafting monomer, and 0.5 to 1 part of initiator.
[0035] Preferably, the grafting monomer is selected from cis-1,2,3,6-tetrahydrophthalic anhydride (TA).
[0036] The initiator comprises a compound initiator A+initiator B.
[0037] More preferably, the initiator A is selected from 4,4,5,5-tetramethyl-2-imidazoline-1-oxyl-3-oxide.
[0038] More preferably, the initiator B is at least one selected from dicumyl peroxide, di-tert-butyl peroxide, benzoyl peroxide, tert-butyl perbenzoate, and diisopropyl peroxydicarbonate.
[0039] As a preferred embodiment, the initiator is selected from 4,4,5,5-tetramethyl-2-imidazoline-1-oxyl-3-oxide complexed with diisopropylbenzene peroxide (NITR-DCP).
[0040] Preferably, in the initiator, the mass ratio of the initiator A to the initiator B is: 1:(1-1.2).
[0041] The invention adopts a nitrogen-oxide-stabilized free radical method, prepares POE grafted cis-1,2,3,6-tetrahydrophthalic anhydride by compounding an initiator, and improves the monomer grafting rate by an "active" free radical polymerization reaction.
[0042] The present invention provides a method for preparing a compatibilizer, and the specific steps are as follows: The materials are weighed according to the set ratio and put into a high-speed mixer for mixing. After mixing, the materials are added to the feed port and added to the twin-screw extruder from the feed port at the set speed, and the reaction extrusion is carried out according to the set conditions. The extrudate is cooled in a cooling water tank and pelletized to obtain a POE grafted TA product (POE-g-TA).
[0043] Preferably, the setting conditions are as follows: the processing temperature is set to 200 ~ 220 ° C, the screw speed is 200 ~ 300 rpm, and the feeding speed is 10 ~ 20 rpm.
[0044] The application and preparation method of the above compatibilizer in nylon is as follows: Weigh 50-70 parts of nylon, 25-40 parts of glass fiber, 3-9 parts of compatibilizer, and 0.2-0.4 parts of antioxidant 1098 and mix them in a high-speed mixer. After mixing, place them in a twin-screw extruder, set the extrusion temperature to 240-280℃, the screw speed to 300-400 rpm, and the feed speed to 10-20 rpm. Cool the extrudate in a cooling water tank and then pelletize to obtain modified nylon pellets.
[0045] Preferably, the nylon is one of nylon 66 and nylon 6.
[0046] The compatibilizer provided by the above technical solution can be applied to thermoplastic plastics.
[0047] In the process of co-processing the compatibilizer and the thermoplastic, processing aids and modifiers conventional in the art are also used, such as flame retardants, lubricants, ultraviolet absorbers, antioxidants, fillers, etc.
[0048] Unless otherwise defined, the meaning of all technical and scientific terms used herein is the same as that generally understood by those of ordinary skill in the art to which the present disclosure belongs. Although methods and materials similar or equivalent to those described herein can be used in the practice or testing of the disclosed composition embodiments, suitable methods and materials are described below. Unless citing a specific paragraph, all publications, patent applications, patents and other references mentioned herein are incorporated herein by reference in their entirety. If a conflict occurs, this specification and the definitions included therein shall prevail. In addition, materials, methods and examples are illustrative only, and not restrictive.
[0049] The technical scheme of the present invention, its implementation process and principle, etc. will be further explained through specific embodiments as follows. It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. The described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. Unless otherwise specified, the reagents and raw materials used in the following examples are commercially available, and the test methods for which specific conditions are not specified are usually carried out under conventional conditions or according to the conditions recommended by the manufacturers. In addition, unless otherwise specified, the experimental methods, detection methods, and preparation methods disclosed in the present invention all adopt conventional techniques in the art. These technologies have been fully described in the existing literature.
[0050] The test methods and standards for the performance parameters of the following embodiments and comparative examples of the present invention are as follows: (1) Grafting rate: The grafting rate of TA in the grafted product was calculated by acid-base titration.
[0051] Weigh 1.0 g of the purified grafted product, heat and reflux in 50 ml of xylene solution for 30 min to fully dissolve the grafted product, then titrate with a 0.1 mol / L KOH-ethanol standard solution, use colorless phenolphthalein test solution as an indicator, add dropwise under continuous stirring, and record the volume V1 of the KOH-ethanol standard solution used when the solution turns red. Then back-titrate with a CH3COOH-ethanol standard solution of the same concentration, stop titrating when the solution changes from red to colorless, and record the volume V2 of the CH3COOH standard solution used. Measure three times according to the above experimental steps and take the average value, and calculate the grafting rate GR according to the following formula: ; Wherein, C is the concentration of KOH and CH3COOH-ethanol standard solution (mol / L); M is the relative molecular weight of TA (g / mol); and m is the mass of the grafted sample to be titrated (g).
[0052] (2) Melt index: Refer to GB / T 3682-2000 standard, use a melt flow rate meter to measure the mass of the sample flowing out of the die of the special equipment within ten minutes, which is the melt index. The test conditions are as follows: temperature 230℃, weight 2.16kg (230℃*2.16 kg). Each sample is tested five times and the average value is taken.
[0053] (3) Mechanical properties: The tensile strength was tested according to ISO 527-1 / -2, the flexural strength and flexural modulus were tested according to ISO 178, and the simply supported beam notched impact strength was tested according to ISO 179 / 1eA.
[0054] The technical solution of the present invention is described in detail below through specific embodiments.
[0055] Example 1 The preparation method of the compatibilizer provided in this embodiment specifically comprises the following steps: Weigh 100 parts of polyolefin elastomer, 6 parts of cis-1,2,3,6-tetrahydrophthalic anhydride, and 0.6 parts of compound initiator (including diisopropylbenzene peroxide and 4,4,5,5-tetramethyl-2-imidazoline-1-oxyl-3-oxide (NITR) in a mass ratio of 1:1), and put them into a high-speed mixer for mixing. After mixing, add the materials to the feed port, set the feed speed to 10 rpm, the processing temperature to 210°C, and the temperature settings of each section of the twin-screw extruder are: 170°C, 180°C, 190°C, 200°C, 205°C, 205°C, 210°C, 210°C, 190°C, and the screw speed is 200 rpm. The extrudate is cooled in a cooling water tank and pelletized to obtain a grafted product, which is compatibilizer 1#.
[0056] The raw material composition and processing conditions of this example are listed in Table 1, and the test results of the product melt index and anhydride grafting rate are listed in Table 1.
[0057] Example 2 The preparation method of the antibacterial agent provided in this embodiment, the ratio of each component and the preparation method are basically the same as those in Example 1, the difference being that the amount of the initiator used in this embodiment is 0.5 parts.
[0058] The obtained grafted product is compatibilizer 2#.
[0059] The raw material composition and processing conditions of this example are listed in Table 1, and the test results of the product melt index and anhydride grafting rate are listed in Table 1.
[0060] Example 3 The component ratio and preparation method of the compatibilizer of this embodiment are basically the same as those of Embodiment 1, except that the amount of the grafting monomer used in this embodiment is 4 parts.
[0061] The obtained grafted product is compatibilizer 3#.
[0062] The raw material composition and processing conditions of this example are listed in Table 1, and the test results of the product melt index and anhydride grafting rate are listed in Table 1.
[0063] Example 4 The component ratio and preparation method of the compatibilizer of this embodiment are basically the same as those of Embodiment 1, except that the amount of the grafting monomer used in this embodiment is 8 parts.
[0064] The obtained grafted product is compatibilizer 4#.
[0065] The raw material composition and processing conditions of this example are listed in Table 1, and the test results of the product melt index and anhydride grafting rate are listed in Table 1.
[0066] Example 5 The component ratio and preparation method of the compatibilizer in this embodiment are basically the same as those in Example 1, except that the processing temperature in this embodiment is 200°C, and the temperature settings of each section of the twin-screw extruder are: 160°C, 170°C, 180°C, 190°C, 195°C, 195°C, 200°C, 200°C, 190°C.
[0067] The obtained grafted product is compatibilizer 5#.
[0068] The raw material composition and processing conditions of this example are listed in Table 1, and the test results of the product melt index and anhydride grafting rate are listed in Table 1.
[0069] Example 6 The component ratio and preparation method of the compatibilizer of this embodiment are substantially the same as those of Embodiment 1, except that the screw speed in this embodiment is 250 rpm.
[0070] The obtained grafted product is compatibilizer 6#.
[0071] The raw material composition and processing conditions of this example are listed in Table 1, and the test results of the product melt index and anhydride grafting rate are listed in Table 1.
[0072] See also Figure 1 , is the infrared spectrum of the compatibilizer POE-g-TA prepared in Example 1 to Example 6. It can be seen from the figure that the wave number is 1780 cm -1 and 1710 cm -1 An obvious characteristic peak appears at the TA structure, corresponding to the C=O stretching vibration peak of the anhydride in the TA structure.
[0073] Comparative Example 1 The component ratio and preparation method of the compatibilizer in this comparative example are substantially the same as those in Example 1, except that the amount of the initiator used in this comparative example is 1.2 parts.
[0074] The obtained grafted product is compatibilizer 1'#.
[0075] The raw material composition and processing conditions of this comparative example are listed in Table 1, and the test results of the product melt index and anhydride grafting rate are listed in Table 1.
[0076] Comparative Example 2 The component ratio and preparation method of the compatibilizer in this comparative example are basically the same as those in Example 1, except that the processing temperature in this comparative example is 230°C, and the temperature settings of each section of the twin-screw extruder are: 170°C, 180°C, 190°C, 200°C, 220°C, 220°C, 230°C, 230°C, 230°C, and 220°C.
[0077] The obtained grafted product is compatibilizer 2'#.
[0078] The raw material composition and processing conditions of this comparative example are listed in Table 1, and the test results of the product melt index and anhydride grafting rate are listed in Table 1.
[0079] Comparative Example 3 The component ratio and preparation method of the compatibilizer in this comparative example are substantially the same as those in Example 1, except that the screw speed in this comparative example is 350 rpm.
[0080] The obtained grafted product is compatibilizer 3'#.
[0081] The raw material composition and processing conditions of this comparative example are listed in Table 1, and the test results of the product melt index and anhydride grafting rate are listed in Table 1.
[0082] Comparative Example 4 The only difference between this comparative example and Example 1 is that the initiator used is 0.6 parts of dicumyl peroxide (DCP), and the other steps and conditions are the same.
[0083] The obtained grafted product is compatibilizer 4'#.
[0084] The raw material composition and processing conditions of this comparative example are listed in Table 1, and the test results of the product melt index and anhydride grafting rate are listed in Table 1.
[0085] Comparative Example 5 The only difference between this comparative example and Example 1 is that the initiator used is 0.6 parts of 4,4,5,5-tetramethyl-2-imidazoline-1-oxyl-3-oxide (NITR), and the other steps and conditions are the same.
[0086] The obtained grafted product is compatibilizer 5'#.
[0087] The raw material composition and processing conditions of this comparative example are listed in Table 1, and the test results of the product melt index and anhydride grafting rate are listed in Table 1.
[0088] Table 1 Raw material composition, processing conditions, grafting rate and melt index of each embodiment and comparative example ; It can be seen from Examples 1, 3 and 4 that the higher the content of the grafted monomer, the higher the grafting rate. This is mainly because the increase in the monomer content can increase the number of effective collisions between it and the grafted resin free radicals, increase the collision probability, and thus increase the grafting rate. However, when the monomer content increases to a certain extent, the increase in the grafting rate tends to be stable. It can be seen from Examples 1, 2 and Comparative Example 1 that with the increase in the amount of initiator added, the grafting rate shows a development trend of first increasing and then decreasing. This is attributed to the fact that the increase in initiator within a certain range is conducive to inducing polymer macromolecules to produce more free radicals, increasing the number of grafting sites on the macromolecular chain, thereby increasing the contact probability with the monomer. However, when the amount of initiator added exceeds a certain limit, it will cause the free radical concentration to be too large, resulting in an intensification of the coupling reaction between the free radicals, which will hinder the grafting reaction between the macromolecular free radicals and the monomer.
[0089] It can be seen from Example 1, Example 5 and Comparative Example 2 that the grafting rate also shows a trend of first increasing and then decreasing with the increase of processing temperature. Combined with theoretical analysis: processing temperature affects the efficiency and activity of grafting reaction by affecting the decomposition rate of the initiator. At lower temperatures, NITR in NITR-DCP tends to covalently bind to the growing free radicals to form dormant species. At this time, the decomposition rate of DCP is also slow, which makes the grafting reaction rate of the system low; as the temperature rises, the NITR dormant species can reversely split to form growing free radicals, while accelerating the decomposition of DCP, so that the composite initiator system can induce the production of more macromolecular free radicals, which is conducive to the occurrence of grafting reaction. When the temperature is too high, excessive macromolecular free radicals can easily cause side reactions such as cross-linking and coupling, which inhibit the grafting reaction.
[0090] It can be seen from Example 1, Example 6 and Comparative Example 3 that when the screw speed is 200 rpm, the grafting rate of the system is the highest. When the screw speed is increased to 350 rpm, part of the initiator will be squeezed out before it has time to decompose and take effect, which is equivalent to a reduction in the effective content of the initiator participating in the reaction, resulting in a significant decrease in the grafting rate.
[0091] The compatibilizers prepared in Example 1 (compatibilizer 1#), Example 2 (compatibilizer 2#), Example 5 (compatibilizer 5#), Example 6 (compatibilizer 6#), Comparative Examples 1 to 3 (compatibilizer 1'# to compatibilizer 3'#) were applied to glass fiber reinforced nylon 66 system, as follows.
[0092] Example 7
[0093] Weigh 67 parts of nylon 66, 30 parts of glass fiber, 3 parts of compatibilizer 1# obtained in Example 1, and 0.3 parts of antioxidant 1098 and put them into a high-speed mixer for mixing. After mixing, put them into a twin-screw extruder, set the extrusion temperature to 270°C, the screw speed to 400 rpm, and the feed speed to 20 rpm. After the extrudate is cooled in a cooling water tank, it is pelletized to obtain modified nylon pellets, and injection molding is used to obtain test specimens. The mechanical properties test results are listed in Table 2.
[0094] Example 8 The preparation method of the modified nylon in this example is basically the same as that in Example 7, except that the compatibilizer in this example is selected from the compatibilizer 2# obtained in Example 2. The mechanical property test results are listed in Table 2.
[0095] Example 9 The preparation method of the modified nylon in this example is substantially the same as that in Example 7, except that the compatibilizer in this example is selected from the compatibilizer 5# obtained in Example 5. The mechanical property test results are listed in Table 2.
[0096] Example 10 The preparation method of the modified nylon in this example is substantially the same as that in Example 7, except that the compatibilizer in this example is selected from the compatibilizer 6# obtained in Example 6. The mechanical property test results are listed in Table 2.
[0097] Comparative Example 6 The preparation method of the modified nylon in this comparative example is basically the same as that in Example 7, except that the compatibilizer in this comparative example is selected from the compatibilizer 1′# obtained in Comparative Example 1. The mechanical properties test results are listed in Table 2.
[0098] Comparative Example 7 The preparation method of the modified nylon in this comparative example is basically the same as that in Example 7, except that the compatibilizer in this comparative example is selected from the compatibilizer 2'# obtained in Comparative Example 2. The mechanical properties test results are listed in Table 2.
[0099] Comparative Example 8 The preparation method of the modified nylon in this comparative example is basically the same as that in Example 7, except that the compatibilizer in this comparative example is selected from the compatibilizer 3'# obtained in Comparative Example 3. The mechanical property test results are listed in Table 2.
[0100] Comparative Example 9 This comparative example is substantially the same as Example 7, except that no compatibilizer is added in this comparative example. The mechanical properties test results are listed in Table 2.
[0101] Comparative Example 10 This comparative example is substantially the same as Example 7, except that the compatibilizer in this comparative example is selected from the compatibilizer 4′# obtained in Comparative Example 4. The mechanical properties test results are listed in Table 2.
[0102] Comparative Example 11 This comparative example is substantially the same as Example 7, except that the compatibilizer in this comparative example is selected from the compatibilizer 5′# obtained in Comparative Example 5. The mechanical properties test results are listed in Table 2.
[0103] Table 2 Test results of various properties of modified nylon resins in various embodiments and comparative examples
[0104] The above are only preferred embodiments of the present invention, which do not limit the protection scope of the present invention. For those skilled in the art, the present invention may have various modifications and changes. Within the spirit and principle of the present invention, changes, modifications, replacements, integrations and parameter changes to these embodiments by conventional substitutions or by being able to achieve the same functions without departing from the principles and spirit of the present invention all fall within the protection scope of the present invention.
Claims
1. A compatibilizer, characterized in that: The invention is composed of a polyolefin elastomer, a grafting monomer and an initiator; wherein the grafting monomer is cis-1,2,3,6-tetrahydrophthalic anhydride.
2. The compatibilizer according to claim 1, characterized in that The added amount of the grafting monomer accounts for 2-10 wt % of the polyolefin elastomer.
3. The compatibilizer according to claim 1, characterized in that The initiator is a compound of initiator A and initiator B; wherein the initiator A is selected from 4,4,5,5-tetramethyl-2-imidazoline-1-oxyl-3-oxide; The initiator B is selected from at least one of dicumyl peroxide, di-tert-butyl peroxide, benzoyl peroxide, tert-butyl perbenzoate, and diisopropyl peroxydicarbonate; And / or, in the initiator, the mass ratio of the initiator A to the initiator B is: 1: (1~1.2).
4. The compatibilizer according to claim 1, characterized in that In parts by mass, the compatibilizer components are as follows: 100 parts of polyolefin elastomer, 2 to 10 parts of the grafting monomer, and 0.5 to 1 part of the initiator.
5. A method for preparing a compatibilizer as claimed in any one of claims 1 to 4, characterized in that: The polyolefin elastomer, grafting monomer and initiator are added to a high-speed mixer for mixing; then, they are fed into a twin-screw extruder through a feeding port, and reaction conditions are set to react and extrude; finally, after cooling, pelletizing is performed to obtain a grafted product, namely POE-g-TA.
6. The preparation method according to claim 5, characterized in that: The reaction conditions include a reaction temperature of 200-220°C; a screw speed of 200-300 rpm; The feeding speed is 10-20 rpm.
7. Use of the compatibilizer according to any one of claims 1 to 4 in the preparation of modified nylon materials.
8. A modified nylon material, characterized in that: The method comprises the compatibilizer as described in any one of claims 1 to 4, nylon, and a toughening agent; the toughening agent is glass fiber.
9. The modified nylon material according to claim 8, characterized in that: In terms of mass ratio, the modified nylon material comprises: 50-70 parts of nylon, 25-40 parts of glass fiber, 3-9 parts of compatibilizer and 0.2-0.4 parts of antioxidant.
10. The modified nylon material according to claim 8 or 9, characterized in that: The nylon is nylon 66 or nylon 6; the antioxidant is antioxidant 1098.
Citation Information
Patent Citations
Preparation method of POE (polyolefin elastomer) chemically-grafted maleic anhydride
CN103450403A
